This is thy brother’s voice : documentary and metadocumentary linguistic work with a folklore recording from the Nenets-Komi contact area - Blokland, Rogier; Partanen, Niko; Rießler, Michael (2021)
In this paper we analyse an epic song, performed by Ulita Koskova in 1966 in Kolva in the Komi ASSR, and recorded by the Hungarian-Australian researcher Erik Vászolyi, and discuss its background and wider historical context. We look at different ways how such material can contribute to data-driven and sociolinguistically oriented research, specifically in connection to contemporary documentary linguistics, and point to directions for further research.